Rare Fetus-in-Fetu: Experience From a Large Tertiary Pediatric Referral Center - Xiaowen, Mao; Lingxi, Cheng; Song, Lin; Shengbao, Pan; Xiaohong, Yang; Xinghai, Yang (Frontiers in Pediatrics, 2021)
Objective: Fetus-in-fetu (FIF) is an extremely rare disease, and most prior publications are single case reports. Here, we describe the clinical characteristics, imaging manifestations, and the treatment and related complications of FIF from a large tertiary pediatric referral center. Materials: After institutional review board approval, patients with a diagnosis of FIF between January 2010 to November 2019 were further selected and reexamined. We analyzed the general clinical characteristics, imaging manifestations, treatment, and prognosis of the patients. Results: A total of seven (four male and three female) patients with FIF were included in the study. All patients were diagnosed with FIF during the antenatal ultrasound examination along with an abnormal increase in alpha fetoprotein, and it was confirmed by subsequent pathological examination. The median gestation period when FIF was first diagnosed was 25 (range: 22–32) weeks. Ultrasound, computed tomography, and magnetic resonance imaging were the main preoperative diagnostic techniques used. All patients underwent FIF resection within one month after birth: four patients had open surgery and three had laparoscopic surgeries (one case was converted to open surgery); only one patient developed ascites after surgery. All patients are growing up healthy and without tumor recurrence at the last follow-up. The level of alpha fetoprotein decreased to normal within one year (range 3-10 months) after surgery performed. Conclusion: As the size of the FIF increases, it can be found and diagnosed in antenatal ultrasound examination. Surgery is an important curative treatment for FIF and generally results in excellent long-term quality of life.